Knowledge of Male Infertility and Acceptance of Medical Assistance Reproductive Technology Among Fertile and Infertile Senegalese Men - Gaye O; Ba K; Diallo M; Niasse A; Counta AL; Ndiaye M; Gning M; Gueye A; Fall PA (Research and Reports in Urology)
Oumar Gaye, Khadidiatou Ba, Mouhamed Diallo, Awa Niasse, Amdy Laye Counta, Modou Ndiaye, Moustapha Gning, Ablaye Gueye, Papa Ahmed Fall Urology Department of Dalal Jamm Hospital, Dakar, SenegalCorrespondence: Oumar Gaye, Urology Department of Dalal Jamm Hospital, Dakar, 21346, Senegal, Tel +221776190954, Email oumargaye-uro@outlook.frPurpose: The objective of our study was to examine the knowledge of male infertility and the acceptance of assisted reproductive technology (ART) methods.Patients and Methods: We conducted a descriptive, comparative, cross-sectional study from April 2023 to August 2023 in a center in Dakar. Included in the study were male patients aged 18 and older followed for male infertility (group 1) and fertile patients of the same age as those in group 1 (group 2). We designed a questionnaire assessing the sociodemographic characteristics of the respondents, their knowledge of male infertility, knowledge of ART, its acceptability, and the source of information about male infertility.Results: Our sample size consisted of 119 respondents for each group. The average age of respondents in both groups was 41.24 ± 8.42 years. Fifty-eight percent of respondents in group 1 were referred by their wife’s gynecologist. Fifty-four percent of respondents in group 1 had a good knowledge of male infertility, and 42.86% had average knowledge of male infertility. The majority of respondents in group 1 (42.9%) and group 2 (40.3%) did not know the duration that defines infertility. Fifty-seven percent of respondents in Group 1 and 81.5% of respondents in Group 2 did not know what assisted reproductive technology meant. Eighty-six percent of respondents in Group 1 agreed to use ART for procreation. The majority of respondents in Group 1 (54.6%) and Group 2 (58.8%) attributed a success rate of between 35% and 75% to ART.Conclusion: Infertile men had better knowledge of male fertility than fertile men. Respondents in both groups, as well as the advanced age of men did not know the duration defining infertility. Poor knowledge of ART was also observed among respondents in both groups, and a better acceptance of ART methods was noted among infertile men.Keywords: knowledge, male infertility, assisted reproductive technology, awareness, Senegal